2013
DOI: 10.1248/bpb.b12-00769
|View full text |Cite
|
Sign up to set email alerts
|

The Permeability of Puerarin Loaded Poly(butylcyanoacrylate) Nanoparticles Coated with Polysorbate 80 on the Blood–Brain Barrier and Its Protective Effect against Cerebral Ischemia/Reperfusion Injury

Abstract: Puerarin (PUE) is a good candidate for treating stroke, but its low concentration in brain after administration limits its curative efficacy. The aim of the present work was to design and characterize PUE loaded poly(butylcyanoacrylate) nanoparticles (PBCN) coated with polysorbate 80 (Ps 80), and to evaluate the effect of PBCN on the permeability of PUE across the blood-brain barrier (BBB) and the effect of PUE loaded PBCN on the cerebral ischemia/reperfusion injury. PUE loaded PBCN were successfully prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 45 publications
(43 reference statements)
0
32
0
Order By: Relevance
“…Coating polysorbate 80 to the surface of nanoparticles has been shown to enhance the efficiency for nanoparticles to interact with BBB through the following mechanisms: (1) binding with apolipoprotein E in the blood and the follow-up endocytosis by endothelial cells, and (2) suppressing the function of P-glycoprotein (P-gp), consequently reducing the efflux of nanoparticles from brain parenchyma [67]. Recent studies have successfully applied this concept both in therapeutics and diagnostics [66, 67]. These polysorbate 80 coated nanoparticles could significantly increase the brain uptake of doxorubicin at 1 hour post administration (nanoparticle with doxorubicin: undetectable amount, polysorbate 80 coated nanoparticle with doxorubicin: 2 µg/g) [87].…”
Section: 1 Targeting Endothelial Cells In the Cnsmentioning
confidence: 99%
“…Coating polysorbate 80 to the surface of nanoparticles has been shown to enhance the efficiency for nanoparticles to interact with BBB through the following mechanisms: (1) binding with apolipoprotein E in the blood and the follow-up endocytosis by endothelial cells, and (2) suppressing the function of P-glycoprotein (P-gp), consequently reducing the efflux of nanoparticles from brain parenchyma [67]. Recent studies have successfully applied this concept both in therapeutics and diagnostics [66, 67]. These polysorbate 80 coated nanoparticles could significantly increase the brain uptake of doxorubicin at 1 hour post administration (nanoparticle with doxorubicin: undetectable amount, polysorbate 80 coated nanoparticle with doxorubicin: 2 µg/g) [87].…”
Section: 1 Targeting Endothelial Cells In the Cnsmentioning
confidence: 99%
“…In addition, utilized coated PEG-based liposomes were also found to be localized to the CA region of the hippocampus, suggesting a probable mode of targeted delivery of reactive oxidative species quenchers in the treatment of stroke (Yun et al, 2013). Zhao et al (2013) have tested Puerarin (PUE), a compound that suffers low availability in brain post-administration, as a candidate drug for treating stroke. In their work, PUE-loaded poly (butylcyanoacrylate) nanoparticles (PBCN) coated with polysorbate 80 (Ps 80), were tested for BBB crossing and effects on the cerebral ischemia/reperfusion injury.…”
Section: Different Applicationsmentioning
confidence: 99%
“…In their work, PUE-loaded poly (butylcyanoacrylate) nanoparticles (PBCN) coated with polysorbate 80 (Ps 80), were tested for BBB crossing and effects on the cerebral ischemia/reperfusion injury. It was found that the vein injection of PUE-loaded PBCN exerted an improved neuroprotective effect in rats with focal cerebral ischemic injury, significantly decreasing neurological deficit and reducing the infarct volumes (Zhao et al, 2013). Similarly, Yin et al (2012) used poly (n-butyl-2-cyanoacrylate) (PBCA) nanoparticles to deliver drugs for treatment of traumatic brain injury (TBI).…”
Section: Different Applicationsmentioning
confidence: 99%
“…This system may also permit a reduction in the dose of the compound that has poor oral bioavailability. Zhao et al (2013) reported that nano-puerarin (PN) improves the oral absorption of puerarin. In this direction, this study aims to develop PN, evaluate its anti-implantation efficacy, and map the molecular cues underlying the contragestive potential.…”
Section: Introductionmentioning
confidence: 99%